Electrochemical and in situ spectroelectrochemical monitoring of the interaction between cobaltphthalocyanines and molecular oxygen in aprotic media - KOCA, ATIF (ELSEVIER SCIENCE SA, 2011)
In this study, voltammetric and spectroelectrochemical measurements of cobaltphthalocyanines (CoPc) bearing different substituents were performed in aprotic solvents to determine the mechanism of interaction between CoPc and molecular oxygen. Metal-based redox processes of the cobaltphthalocyanine complexes indicate their possible electrocatalytic activities toward many target species. Different substituents of the complexes affect the peak characters and assignments of the processes. Presence of O-2 in the electrolyte system influences oxygen reduction reaction and the electrochemical and spectral behaviors of the complexes, which indicate homogeneous electrocatalytic activity of the complexes for the oxygen reduction reaction. In situ electrocolorimetric method was applied to investigate color of the anionic and cationic forms of the complexes. Electrochemical and in situ spectroelectrochemical analysis indicate interaction of molecular oxygen with monoanionic [(CoPc-2)-Pc-1](1-) and presence of an equilibrium between the reactants [(CoPc-2)-Pc-1](1-) and O-2 and the intermediates [O-2(-)-(CoPc2-)-Pc-II](-) and [O-2(2-)-(CoPc2-)-Pc-II](2-). This equilibrium is disturbed in desired direction by changing the excitation signals of the voltammetric and spectroelectrochemical techniques. The intermediates are very unstable, regenerating the starting form of the catalyst and the products O-2(-) and O-2(2-). Interaction rate of O-2 with the complexes is significantly influenced with the steric and coordination properties of the substituents and solvent of the system. Voltammetric and spectroelectrochemical results indicate that homogeneous electrocatalytic ORR follows an inner sphere chemical catalysis process. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cobaltphthalocyanine; Oxygen reduction reaction; Electrocatalyst; Spectroelectrochemistry; ELECTROCATALYTIC ACTIVITY; THIN-FILMS; COBALT PHTHALOCYANINE; HYDROGEN-PRODUCTION; SUBSTITUTED COBALT; REDOX CATALYSIS; CARBON-DIOXIDE; REDUCTION; COMPLEXES; SOLVENTS